A sound brand name: The role of voiced consonants in pharmaceutical branding. (June 2021) - Park, Jaewoo; Motoki, Kosuke; Pathak, Abhishek; Spence, Charles
Highlights: Sound symbolism provides a useful framework when developing pharmaceutical brand name. Voiced (vs. voiceless) consonants in brand names increase expected efficacy of medicine. Perceived potency and activity mediate the effect of voiced sound on medicine's expected qualities. Abstract: Given the worldwide growth of the over-the-counter (OTC) drug market and the increase in the direct-to-consumer advertising of medicines, pharmaceutical branding has become an increasingly important component affecting the consumer's beliefs about, and hence their responses towards, OTC medicines. The brand name is one of the most important external cues for brand evaluation and influences various aspects of consumer-brand association (e.g., perceived quality/efficacy, brand attitude, and brand image). Although sound symbolism, which refers to the non-arbitrary association that exists between particular sound sequences and specific meanings in speech, has proven to be an effective means of creating successful brand names in a wide range of products, surprisingly little attention has been paid to its application in the case of pharmaceutical branding. In this study, we systematically investigated whether and how consonants in drug brand names influence consumers' medicine expectancies (e.g., medicinal power, long-lasting efficacy). Across three experiments, a robust effect of voiced (vs. voiceless) consonants present in brand names on the perceived potency and activity for target medicines was found. In addition, the results also revealed that voiced (vs. voiceless) consonants increase the expectancies of medicine effectiveness, duration of medicine activity, price, and potential side effects. Furthermore, we found that the perceived potency and activity for brand names significantly mediated the effect of voiced consonants. Taken together, these findings enhance our understanding of the role of consonant sound symbolism in brand name development and can potentially help pharmaceutical firms to create appropriate brand names that can effectively communicate information concerning a medicine's properties.